2013
DOI: 10.9775/kvfd.2013.8627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yucca schidigera Spraying in Different Litter Materials on Some Litter Traits and Breast Burn of Broilers at the Fifth Week of Production

Abstract: SummaryThis study was carried out to determine the effects of different levels of Yucca schidigera spraying in different litter materials on some litter traits (moisture, pH, ammonia, total colony count, number of Enterobacteriaceae and number of yeast and mold) and breast burn of broilers at the 5 th week of production. A total of four hundred thirty two 1-d-old male broiler chicks (ROSS-308) were used. In this study 12 chicks were put in each pen having 170x94x90 cm (depth x length x height). Half of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…When YSE was applied to laying-hens, 100 ppm inclusion in diets significantly reduced ammonia emission by 44% and 28% for the first two days of manure storage 52 . However, an experiment showed that ammonia N concentrations and microorganism levels of litter materials (half was wood shavings, the other was rice hull) among examined groups did not show statistical difference when pulverized YSE was applied to different litter materials at the level of 0, 4% and 8% 53 . It was hypothesized that the efficiency of YSE could be amplified if litter was used in farming houses under bad situations 53 .…”
Section: In Monogastric Animalsmentioning
confidence: 91%
See 2 more Smart Citations
“…When YSE was applied to laying-hens, 100 ppm inclusion in diets significantly reduced ammonia emission by 44% and 28% for the first two days of manure storage 52 . However, an experiment showed that ammonia N concentrations and microorganism levels of litter materials (half was wood shavings, the other was rice hull) among examined groups did not show statistical difference when pulverized YSE was applied to different litter materials at the level of 0, 4% and 8% 53 . It was hypothesized that the efficiency of YSE could be amplified if litter was used in farming houses under bad situations 53 .…”
Section: In Monogastric Animalsmentioning
confidence: 91%
“…However, an experiment showed that ammonia N concentrations and microorganism levels of litter materials (half was wood shavings, the other was rice hull) among examined groups did not show statistical difference when pulverized YSE was applied to different litter materials at the level of 0, 4% and 8% 53 . It was hypothesized that the efficiency of YSE could be amplified if litter was used in farming houses under bad situations 53 . As a study to evaluate the effects of YSE on poultry manure alone or together with microbial preparation, YSE showed highest potentials in reducing volatile odorous compounds concentrations after 96 h of the process 19 .…”
Section: In Monogastric Animalsmentioning
confidence: 91%
See 1 more Smart Citation
“…Another unconventional treatment in the production of broilers is the use of Y. shidigera extract. Authors reported that there was no statistical difference in the values of pH, moisture and ammonia between litters treated with Y. shidigera extract and untreated litters [31].…”
Section: Unconventional Treatmentsmentioning
confidence: 98%
“…Some litter treatments did not have more than one published article so they were excluded from the meta-analysis, namely: enzymatic biocatalyst (Rydall) and bacterial culture (Mizuho) [30]; Yucca Shidigera extract [31]; non-absorbent polymers [32] and biodegradable treatment [33]. Table 1 Shows the characteristics of the studies included in the meta-analysis.…”
Section: Plos Onementioning
confidence: 99%